Community Roles in Advancing Ecological Justice and Inclusive Islamic Education - Jamal Syarif; Siti Muflichah; Mhd Rasid Ritonga; Puji Rahayu (Program Pascasarjana IAIN Langsa, 2026)
Despite the growing scholarship on inclusive education, environmental sustainability, and Islamic educational values, studies examining the interrelationship among ecological justice, disability inclusion, and community participation within Islamic education remain fragmented. Existing research tends to address these dimensions separately, resulting in a limited understanding of how they can be integrated into a coherent educational framework. This study aims to analyze the relationship between ecological justice and inclusivity in Islamic education and to identify the mechanisms through which community participation contributes to the development of a sustainable and equitable educational ecosystem. This study employs a qualitative Systematic Literature Review using the Community Guide Systematic Reviews (CGSR) framework. A total of 32 peer-reviewed articles indexed in Scopus and Web of Science published during the last five years were systematically selected and analyzed through thematic synthesis. The findings reveal that Islamic education possesses a strong normative foundation for promoting ecological justice and disability inclusion through the principles of mizan (balance), rahmah (compassion), and maslahah (public benefit). However, the implementation of these values is constrained by interconnected structural and cultural barriers, including limited institutional capacity, insufficient teacher preparedness, fragmented curriculum integration, and persistent social stigma toward disability. The review further demonstrates that community participation functions as a critical enabling mechanism that bridges the gap between Islamic values and educational practice by strengthening social support, institutional capacity, and environmental awareness. Based on this synthesis, the study proposes the Pendidikan Islam Berbasis Komunitas (PIBK) Model as a conceptual framework integrating Islamic values, inclusive educational practices, ecological responsibility, and collaborative community governance. This model represents the main theoretical contribution of the study by providing an integrative approach for advancing socially inclusive and ecologically sustainable Islamic education. The findings offer implications for curriculum development, teacher training, community empowerment, and educational policy reform in muslim societies.